Selection of method in construction industry by using AHP method - Nur Syafikah, Nasrudin (2018)
Method in construction industry is very important in construction industry. The type of method used in construction may affect the quality of the project. The method that discuss in this research are traditional method, design and build and industrial building system. According to (Sutt. J., 2011), in the traditional procurement method, the client will enter into the contracts separately with architect and contractor. The architect will responsible for design work, while contractor will responsible for construction work. Hence, design and build is contractor accepts responsibility for some or all of the design and for industrial building system is construction system that is built using pre-fabricated components. The objectives of this study are to identify the criteria and suitability for selecting delivery method in construction by Analytical Hierarchy Process (AHP) method. Analytical Hierarchy Process (AHP) is to determine the weights of importance of the parameters. The data concluded, the contractor for Grade 7 is suitable to use industrial building system method and traditional method is suitable for the contractor Grade 1.